Legal Recognition of Hidden Disabilities in Higher Education - Maura Olivia Azzahra; Nayazea Cleo Elvaretta; Fiantika Arla Rahmania; Siti Marátus Rahimatin; Prajna Eka Galuh (Universitas Negeri Surabaya, 2026)
Hidden disabilities often receive limited attention in inclusive education because they are difficult to identify, creating barriers to academic accommodations in higher education. Although Indonesia has regulations protecting the rights of persons with disabilities, its legal framework does not specifically regulate administrative recognition mechanisms for hidden disabilities. This study examines the absence of normative and administrative standards for recognizing hidden disabilities in higher education, which hinders the effective implementation of disability rights. Using a normative juridical method with statutory, conceptual, and human rights approaches, this research analyzes Indonesian disability regulations and relevant international human rights instruments. The findings show that existing legal protections remain inadequate because they lack adaptive recognition procedures that ensure equal access to academic support. This article proposes the Inclusive Hidden Disability Recognition System (IHDRS) as a normative-administrative framework to strengthen inclusive education governance. The study's novelty lies in positioning administrative recognition as an essential component of disability rights protection and establishing a legal framework linking human rights principles with institutional recognition mechanisms for students with hidden disabilities.